Association of Nrf2-encoding NFE2L2 haplotypes with Parkinson's disease - Nilsson Michael; Blennow Kaj; Kurzawski Mateusz; Bialecka Monika; Drozdzik Marek; Nissbrandt Hans; Håkansson Anna; Bergström Petra; Celojevic Dragana; Nilsson Staffan; Landgren Sara; von Otter Malin; et al. (BMC, 2010)
Abstract Background Oxidative stress is heavily implicated in the pathogenic process of Parkinson's disease. Varying capacity to detoxify radical oxygen species through induction of phase II antioxidant enzymes in substantia nigra may influence disease risk. Here, we hypothesize that variation in NFE2L2 and KEAP1, the genes encoding the two major regulators of the phase II response, may affect the risk of Parkinson's disease. Methods The study included a Swedish discovery case-control material (165 cases and 190 controls) and a Polish replication case-control material (192 cases and 192 controls). Eight tag single nucleotide polymorphisms representing the variation in NFE2L2 and three representing the variation in KEAP1 were chosen using HapMap data and were genotyped using TaqMan Allelic Discrimination. Results We identified a protective NFE2L2 haplotype in both of our European case-control materials. Each haplotype allele was associated with five years later age at onset of the disease (p = 0.001) in the Swedish material, and decreased risk of PD (p = 2 × 10-6), with an odds ratio of 0.4 (95% CI 0.3-0.6) for heterozygous and 0.2 (95% CI 0.1-0.4) for homozygous carriers, in the Polish material. The identified haplotype includes a functional promoter haplotype previously associated with high transcriptional activity. Genetic variation in KEAP1 did not show any associations. Conclusion These data suggest that variation in NFE2L2 modifies the Parkinson's disease process and provide another link between oxidative stress and neurodegeneration.